Community Colleges and Employers: How Can We Understand their Connection?. Issue 4 (October 2016) - Osterman, Paul; Weaver, Andrew
Abstract : This paper uses an original, nationally representative survey of manufacturing establishments to shed light on the interaction of employers with community colleges, including information on skill requirements and human resource practices. We test three hypotheses: that high‐skill employers use community colleges, that community colleges are a substitute for employer‐based training, and that community colleges are a complement to so‐called "high‐road" or "high‐commitment" human resource practices. We find limited utilization of community colleges by employers, but those that do establish a relationship are generally satisfied. Employers that demand high skills are more likely to use community colleges, as are "high‐commitment" firms.